1994
DOI: 10.1111/j.1524-4725.1994.tb03193.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Various Degreasing Agents Used in Trichloroacetic Acid Peels

Abstract: Acetone was not found to be superior to the other agents. Furthermore, the flashpoint of acetone is markedly lower than the others, making it more flammable and hazardous in the workplace. The use of alternative degreasers may lessen or eliminate this hazard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…Firm pressure is applied during defatting to ensure complete stripping of the stratum corneum. There is evidence to support that the above may be accomplished with Hibiclens (19).…”
Section: Methodsmentioning
confidence: 99%
“…Firm pressure is applied during defatting to ensure complete stripping of the stratum corneum. There is evidence to support that the above may be accomplished with Hibiclens (19).…”
Section: Methodsmentioning
confidence: 99%
“…Efficacy of the 4 agents was assessed by clinical and histologic examination, which showed no significant difference between treatments. These authors concluded that while acetone is one of the most common agents employed, its lack of superior efficacy and lower flashpoint argue against its widespread use, 31 although, of course, flashpoint is less relevant in chemexfoliation.…”
Section: Chemexfoliationmentioning
confidence: 99%
“…Vor-und Nachbehandlung sind ausschlaggebend für das Peelergebnis. Mit tretinoinhaltigen Cremes werden der Fettgehalt und der pH-Wert der Haut vor dem Peel gesenkt [32,39], die Korneozytenadhäsion wird verringert und die Epidermolyse gefördert, damit sich die Wirkung der Peelsubstanz gleichmäßig in Epidermis und Dermis entfalten kann. Tretinoin bewirkt außer-dem eine erhöhte Mitoserate der Keratinozyten und gewährleistet eine kürze-re Reepithelialisierungsphase nach dem Peel [30,32].…”
Section: Vorbehandlung Für Chemical Peelsunclassified